From forced flexibility to forced labour: the exploitation of migrant workers in Finland - Ollus, Natalia (Publication series, 2016)
This research focuses on the exploitation of migrant workers and trafficking in human beings for the purpose of forced labour in Finland. This thesis consists of a summary and four original articles. The theoretical framework is twofold. First, in order to contextualise the situation of migrant workers, the research addresses changes that globalisation has brought to the economy and the labour markets. Second, the research approaches the exploitation of migrant workers through the framework of corporate crime in order to explore why such crimes remain under-enforced.